On the discursive self-construction of expats, behavior and values - Marianna Lya Zummo (Scripta Manent, 2018)
Considering that learners engage in the creation of new educational scenarios, often using digital media, travelogues have been analysed because they represent the digital development of a well-established genre within tourism discourse. This study focuses on the discursive construction of expats as 1) integrated tourist and 2) travelogue writers. I consider the occurrence of an Us as opposed/assimilated with a Them in the expression of values, behaviors and spaces by analyzing a corpus made up of articles taken from the most accessed travel webzines for expats at the time of the research. Then I analyse the thematic structures and techniques of this textual typology. The paper may help to address pedagogical issues such as critical genre awareness and identity construction.